1999
DOI: 10.1023/a:1021345800325
|View full text |Cite
|
Sign up to set email alerts
|

The most recent dreams of children ages 8–11.

Abstract: The present study examined whether the Most Recent Dream Method is afeasible choice for dream collectionfrom children as young as 8 years old. A quantitative analysis of 30 Most Recent Dreams from 8-11 year-old girls and 32 Most Recent Dreams from 8-11 year-old boys reveals that the method seems feasible as indicated by children's ability to respond. The basic findings for recency, length, types of characters, and other content categories show the same overall pattern of gender similarities and differences by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
20
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 12 publications
8
20
0
Order By: Relevance
“…Several of the empirical papers in this special issue add support to the continuity hypothesis. Saline (1999) notes that the gender differences she found in the Most Recent Dreams of children between the ages of 8 and 11 fit with findings on the emergence of gender differences in this age group. Strauch and Lederbogen (1999) find that the number of same-sexed peers increases in dreams at about the same time that young adolescents become more peer oriented and socialize in same-sex peer groups.…”
Section: The Continuity Hypothesissupporting
confidence: 63%
“…Several of the empirical papers in this special issue add support to the continuity hypothesis. Saline (1999) notes that the gender differences she found in the Most Recent Dreams of children between the ages of 8 and 11 fit with findings on the emergence of gender differences in this age group. Strauch and Lederbogen (1999) find that the number of same-sexed peers increases in dreams at about the same time that young adolescents become more peer oriented and socialize in same-sex peer groups.…”
Section: The Continuity Hypothesissupporting
confidence: 63%
“…In addition to demonstrating the many possibilities for developing new findings with the Hall and Van de Castle coding system, this special issue extends the usefulness of a new approach for collecting good dream samples to children as young as ages 10-11 (Avila-White, Saline, 1999). Termed the Most Recent Dream (MRD) Method, it simply asks everyone in a group setting to write down the Most Recent Dream they can remember, "whether it was last night, last week, or last month" (Domhoff, 1996, p. 67).…”
Section: A New Approach To Collecting Dream Reportsmentioning
confidence: 96%
“…In younger children (8 yrs. and younger), two studies with small sample sizes (Saline, 1999;Sándor, Szakadát, Kertész, & Bódizs, 2015) showed no difference regarding the percentage of physical aggression, however Honig and Nealis (2012) reported that fighting and chasing were prominent in 3 to 5 year-old boys compared to girls in this age group. However, the sample sizes of several studies were very small, e.g., N = 24 (Strauch & Lederbogen, 1999) or N = 40 (Sándor et al, 2015) and replications in larger samples are needed.…”
mentioning
confidence: 96%